Modern Fruit Culture - S.Barooah; S.Barooah (Ludhiana Kalyani, 1995)
This book is primerily inted for agriculture degrees students for studying fundamentals and principles of pomology.
Mechanism of flowering Auxin in plant development Floral Biology of Plants
Keywords: Mechanism of flowering ,Auxin in plant development, Floral Biology of Plants